Improving the Efficiency and Quality of Education as the Basis for Successful Digitalization of the Economy - I. I. Shpak; S. N. Kasanin; A. S. Stepanets (Цифровая трансформация, 2024)
The determining influence of the effectiveness and quality of education systems on all spheres of human activity has been studied: economic, social, socio-political, everyday and spiritual. The most important conditions are considered and the main ways are analyzed to significantly increase the efficiency of modern vocational education while simultaneously improving its quality. The necessity of using adaptive educational technologies is   substantiated, the features of algorithmization of the adaptive learning process are shown in order to improve its quality, and ways of creating an effective model of the professional field for adaptive educational systems are  analyzed. The comparative analysis method was used to select these paths. The possibilities of creating modern adaptive vocational training systems based on the use of the concept of the International Labor Organization “Labor Competency Modules” are illustrated. Examples of results obtained during many years of professional activity are given.